Everyday Future of Yore: Alternative Masculinity in the Lepcha Folktales of Darjeeling (HIMALAYA, 2022)
Gender in the contemporary everyday life of the Darjeeling men is a ritual of reiterating the colonial hypermasculinity that ultimately reinforces the stereotyped notion that the Gorkha men are muscular men whose hegemonic masculinity makes them merely worthy of wars. This toxic masculinity is the major object of criticism by the ecofeminists who have shown how detrimental this hypermasculinity is for both women and ecology. This article, by revisiting the alternative textuality of everydayness as manifested in the select Lepcha folktales of the Hills, aims at uncovering an endogenous eco (alternative)masculinity that may act as a genderqueer model based on which the Gorkha men may learn to replace their colonial internalized ‘ethic of daring’ with the ‘ethic of caring’ in their everyday future. As an interpretation of the folktales by a ‘non-indigenous ally,’ a hybrid methodology has been used by combining various perspectives from the theories related to gender and sexuality, ethno-poetics, folkloristics, etc. The article begins by arguing that the scope of studying everyday life has to be expanded from merely focusing on the micro and the oblivious towards accommodating the hidden ‘non-everyday’ inclusive alternatives that are embedded in the everyday textuality of the folktales. Thereafter, it tries to assert how the politicization of the possible everyday based on an understanding of the history of mentality as revealed through the folktales, can initially, allow the Darjeeling men to recall ‘the not yet-real,’ but plausible, genderqueer male identities of yore. This might eventuallyencourage them to turn the everyday,contemporary space of a martial, Gorkha-hypermasculinity into a multivocal everydayness of alternatives in the near future,with the ‘gentlemen warrior’ evolving into eco-men who, along with aposthuman intimacy, arecompetent in nurturing the feminine and the ecology.